Exploratory Data Analysis of Indonesian Presidential Election Candidate Campaign in 2019 on Twitter - Hermawan, Fadlan Bima; Sutanto, Taufik Edy; Santoso, Ary (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Social media users in Indonesia are growing over time, this has caused many political actors, both individuals, and political parties, to take advantage of this. According to Hootsuite (We are Social) in the Digital 2022 report, Indonesia has 191 million active social media users, so there will be many political actors campaigning on social media. In the literature that discusses similar topics, it is rare to analyze comprehensive exploratory data analysis such as text analysis, hashtags, and social network analysis. From the data analysis conducted in the 2019 Election, the following results were obtained. In text analysis, the narratives used by the two candidates were very different, it was seen that some used other positive and negative narratives. The hashtag analysis found that consistency in campaigning had an influence on electability in the election. In the analysis of social networks, it is found that users who influence social media campaigns, users who appear are not only politicians but also ordinary people who try to support their chosen candidate. The research conducted is expected to be a basic reference in exploring data on social media in other cases, especially in the political field